If There is No Religion: L. Kołakowski’s Defence of the Sacred. Part 2 a polemic - Krzysztof Bochenek; Cezary Mordka; Józef Stala (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The article is an argument with the main theses presented by L. Kołakowski in his vision of religion. The discussion, which considers the strengths of the Polish philosopher’s analyses, concerns the distinction between empiricism and transcendentalism, the epistemological status of empirical sciences and broadly understood naturalisms, as well as the question of metaphysical horror as understood by L. Kołakowski. The text analyses the anthropological argument and the specificity of religion with its personal trust, the specificity of human existence, the experience of the sacred-profane and the importance of religion for human existence. The conclusion presents a further perspective for the analysis of the phenomenon of religion.